What will the weather be like today? - Rogers, Paul, 1950-; Kazuko (New York : Greenwillow Books, 1990)
Animals and humans discuss, in rhyming verse, the possibilities of the day's weather.
"First published in Great Britain in 1989 by Orchard Books"--T.p. verso.
School Library Journal
Horn Book
1.6
K-3
Keywords: Weather -- Juvenile literature; Weather; Weather